The Faroe Islands’ Security Policy in a Process of Devolution - Beinta í Jákupsstovu, 1951-; Berg, Regin (2012)
Fræðigrein Since the late 1990s there has been a remarkable change in the institutional context of safety and security policies for the Faroes. The end of the Cold War led to a reduction in the strategic importance of, and military presence in, the islands. However, today Faroese sea and air space is increasingly exposed to heavy civilian traffic due to expected oil production as well as new sailing routes from the High North. The Faroese government is in a process, nearly completed, of taking over the full responsibility for societal security policy, a field it used to share with the Danish state authorities. In April 2002, the Faroese authorities took over the responsibility for SAR in Faroese sea territory and established a MRCC Center in Tórshavn. A new civic security law was passed by Løgtingið (the parliament) in May 2012. This article discusses micro-states’ options in the international arena; provides a brief overview of the history of Faroese security policy; and discusses the present and future challenges involved in assuring protection and rescue services for the Faroese region of the North Atlantic. Keywords: Faroese autonomy; micro-states; security policy; SAR